Measuring Compliance Therapy in Type 2 Diabetes Mellitus Patients using Proportion of Days Covered (PDC) Method and Its Effect on Clinical Outcomes - Anwar, Irvan -; Sabarudin, Sabarudin; Malina, Rachma; Widaningsih, Ayu Dewi; Wijaya, Aurelia Arbaleta; Nurawaliah, Lilis (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2024)
Diabetes Mellitus (DM) is a chronic disease that occurs when blood glucose levels rise beyond normal limits because the body is unable to produce or use insulin effectively. Therapeutic adherence is one of the causes of normal blood glucose levels and the success of patient therapy. Measurement of therapeutic adherence of dm type 2 patients needs to be carried out to monitor the success of their therapy. This study aims to determine the adherence of antidiabetic therapy using the Proportion of Days Covered (PDC) method and its effect on the clinical outcomes of type 2 DM patients at Sulawesi Tenggara. The research method used is observational research with a descriptive design approach. The sample of this study was 186 people obtained using the Slovin formula. Patients are said to be adherence if their PDC value ≥ 80% and are said to be non-adherence if their PDC value < 80%. The data were analyzed using the chi square test. The results showed that patients adhering to treatment amounted to 130 people (69.9%), while patients who did not comply with treatment amounted to 56 people (30,1%) and there was a significant influence between adherence to antidiabetic therapy on the success of therapy (clinical outcome) with p value = 0.000 in type 2 DM patients at Sulawesi Tenggara. It was be concluded that most of the patients in this study were adherent to the treatment and there was a significant influence between the adherence of antidiabetic therapy to the success of the therapy (clinical outcomes)